[George Gowgani at desk] (1990)
George Gowgani sits at his desk wearing a blazer and a shirt with a tie with his hands folded together. He wears a watch with a dark face on his left hand. Placed on the desk is an office phone, various mugs, a pair of glasses, and paperwork. There is an office plant located in the back corner of the office.